THE USE OF THE MULTISENSORY METHOD NUMICON IN LEARNING BASIC MATHEMATICAL SKILLS BY STUDENTS WITH MODERATE MENTAL DISABILITIES - Krauce, Antra (Education Reform: Education Content Research and Implementation Problems, 2019)
The article “The use of the multisensory method Numicon in learning basic mathematical skills by students with moderate mental disabilities” briefly analyses basic math learning skills of the student with moderate mental disabilities and gather the teaching methods that can be used by teachers. The multisensory method Numicon is described in detail how it can be used in work with the students with moderate mental disabilities. The description of the author’s methodological material “Mathematics with Numicon” is also provided. The results of the research are summarized about the basic mathematical skills for the students with moderate mental disabilities by using the multisensory method and the Numicon materials, and authors methodological material  “Mathematics with Numicon”.